Choosing the Light Meal: Real-Time Aggregation of Calorie Information Reduces Meal Calories. (October 2021) - VanEpps, Eric M.; Molnar, Andras; Downs, Julie S.; Loewenstein, George
Numeric labeling of calories on restaurant menus has been implemented widely, but scientific studies have generally not found substantial effects on calories ordered. The present research tests the impact of a feedback format that is more targeted at how consumers select and revise their meals: real-time aggregation of calorie content to provide dynamic feedback about meal calories via a traffic light label. Because these labels intuitively signal when a meal shifts from healthy to unhealthy (via the change from green to a yellow or red light), they prompt decision makers to course-correct in real time, before they finalize their choice. Results from five preregistered experiments (N = 11, 900) show that providing real-time traffic light feedback about the total caloric content of a meal reduces calories in orders, even compared with similar aggregated feedback in numeric format. Patterns of ordering reveal this effect to be driven by people revising high-calorie orders more frequently, leading them to choose fewer and lower-calorie items. Consumers also like traffic light aggregation, indicating greater satisfaction with their order and greater intentions to return to restaurants that use them. The authors discuss how dynamic feedback using intuitive signals could yield benefits in contexts beyond food choice.